2018
DOI: 10.1097/ncc.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Advanced Prostate Cancer Decision Making Utilizing an Interactive Decision Aid

Abstract: Decision aids assist patients, decision partners, and healthcare providers make satisfying treatment decisions that affect quality/quantity of life. These findings are important for understanding the experiences of patients who have to make difficult decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…Similar to a study in localized prostate cancer 19 and a study of patients with advanced prostate cancer, 20 we found that most patients relied heavily on their physician’s recommendations. However, another study in localized disease found that patients relied more on the stories and experiences of others, particularly men who have been previously treated for localized prostate cancer.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Similar to a study in localized prostate cancer 19 and a study of patients with advanced prostate cancer, 20 we found that most patients relied heavily on their physician’s recommendations. However, another study in localized disease found that patients relied more on the stories and experiences of others, particularly men who have been previously treated for localized prostate cancer.…”
Section: Discussionsupporting
confidence: 82%
“…We identified many similar treatment considerations among men with mPCa, highlighting significant overlap in what patients consider while making treatment decisions for prostate cancer across the disease continuum. Similar to a study in localized prostate cancer 19 and a study of patients with advanced prostate cancer, 20 we found that most patients relied heavily on their physician's recommendations. However, another study in localized disease found that patients relied more on the stories and experiences of others, particularly men who have been previously treated for localized prostate cancer.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Sexuality, masculinity and marital relationship were important issues; the need to encourage communication about these essential areas, throughout the trajectory, was emphasised repeatedly. Due to the complexity and several new treatments, the diagnostic and treatment phase can be complicated and disjointed, involving difficult treatment decisions and multiple care interventions by different HCPs (Jones et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Still, it has been shown that men with mCRPC lack enough information about the treatments and their possible impact of them on their life (Jenkins et al, 2019). Further, QoL has been shown to be more important to men with mCRPC than extending life expectancy with the risk of experiencing debilitating treatment complications (Jones et al, 2018). Considering the often long course of the disease, the severe symptom burden and the decline of QoL in the advanced stages, it has been argued that palliative care might be especially suitable for men with PC, even in conjunction with life-prolonging treatments (Sanford et al, 2013).…”
Section: Introductionmentioning
confidence: 99%